2021
DOI: 10.1093/ajcp/aqab041
|View full text |Cite
|
Sign up to set email alerts
|

Digital Droplet PCR for SARS-CoV-2 Resolves Borderline Cases

Abstract: Objectives The Bio-Rad SARS-CoV-2 ddPCR Kit (Bio-Rad Laboratories) was the first droplet digital polymerase chain reaction (ddPCR) assay to receive Food and Drug Administration (FDA) Emergency Use Authorization approval, but it has not been evaluated clinically. We describe the performance of ddPCR—in particular, its ability to confirm weak-positive severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) results. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Their recommendations also include monitoring patients’ viral loads ( 150 ), as studies have associated lower infectivity with a decrease in the SARS-CoV-2 viral load ( 151 153 ). Since dPCR has the capability of absolute quantification, it has been used to monitor viral loads of patients and to monitor disease progression in COVID-19 patients during hospitalization and after discharge ( 23 , 69 , 76 , 129 , 147 , 154 ). For example, after analyzing the viral loads in various clinical samples, Yu et al ( 69 ) discovered that the viral loads in the sputum samples of patients could reflect COVID-19 disease progression in vivo .…”
Section: Synoptic Overview Of Sars-cov-2 Rt-dpcr Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their recommendations also include monitoring patients’ viral loads ( 150 ), as studies have associated lower infectivity with a decrease in the SARS-CoV-2 viral load ( 151 153 ). Since dPCR has the capability of absolute quantification, it has been used to monitor viral loads of patients and to monitor disease progression in COVID-19 patients during hospitalization and after discharge ( 23 , 69 , 76 , 129 , 147 , 154 ). For example, after analyzing the viral loads in various clinical samples, Yu et al ( 69 ) discovered that the viral loads in the sputum samples of patients could reflect COVID-19 disease progression in vivo .…”
Section: Synoptic Overview Of Sars-cov-2 Rt-dpcr Applicationsmentioning
confidence: 99%
“…However, this method has not been widely used due to the limited sensitivity of RT-qPCR in testing samples with low viral loads. It has also been suggested that RT-dPCR may be more effective than RT-qPCR in pooled samples due to its higher sensitivity, specificity, and precision; same-day turnaround time; and relatively low cost ( 23 , 164 , 165 ). To test the suitability of RT-dPCR for pooling, Martin et al divided 448 COVID-19 hospital samples into three groups (14 pools of 32 samples/pool, 28 pools of 16 samples/pool, and 56 pools of 8 samples/pool) for RT-dPCR testing and directly compared the results to those of individual testing by RT-qPCR ( 165 ).…”
Section: Synoptic Overview Of Sars-cov-2 Rt-dpcr Applicationsmentioning
confidence: 99%
“…The studies were conducted worldwide; 16 in Asia [ 12 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], 14 in Europe [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], and 9 in North America [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. A minority of studies (8) included control samples [ 21 , 28 , 29 , 33 , 38 , 47 , 54 , 56 ]. One study did not report the number of samples or patients studied [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Samples were transported to an APL laboratory at room temperature and tested upon receipt using one of the following assays: BD MAX SARS-CoV-2 (BD Company, Sparks, MD), Xpert Xpress SARS-CoV-2 (Cepheid, Sunnyvale, CA), Seegene Allplex 2019-nCoV (Seegene Inc., Seoul, Korea) or the APL developed RT-PCR test (text, Supplemental Digital Content 1; http://links.lww.com/INF/E699 ). Archived samples, which were stored at −70°C, were tested by ddPCR using the validated 3 Bio-Rad SARS-CoV-2 ddPCR Kit (Bio-Rad, Pleasanton, CA, USA) (text, Supplemental Digital Content 2; http://links.lww.com/INF/E699 ).…”
Section: Methodsmentioning
confidence: 99%